Bacterial flagellum as a propeller and as a rudder for efficient chemotaxis - Xie, Li (National Academy of Sciences, 2011)
We investigate swimming and chemotactic behaviors of the polarly flagellated marine bacteria Vibrio alginolyticus in an aqueous medium. Our observations show that V. alginolyticus execute a cyclic, three-step (forward, reverse, and flick) swimming pattern that is distinctively different from the run–tumble pattern adopted by Escherichia coli. Specifically, the bacterium backtracks its forward swimming path when the motor reverses. However, upon resuming forward swimming, the flagellum flicks and a new swimming direction is selected at random. In a chemically homogeneous medium (no attractant or repellent), the consecutive forward t(f) and backward t(b) swimming times are uncorrelated. Interestingly, although t(f) and t(b) are not distributed in a Poissonian fashion, their difference Δt = |t(f) - t(b)| is. Near a point source of attractant, on the other hand, t(f) and t(b) are found to be strongly correlated, and Δt obeys a bimodal distribution. These observations indicate that V. alginolyticus exploit the time-reversal symmetry of forward and backward swimming by using the time difference to regulate their chemotactic behavior. By adopting the three-step cycle, cells of V. alginolyticus are able to quickly respond to a chemical gradient as well as to localize near a point source of attractant.